1995
DOI: 10.2527/1995.7351396x
|View full text |Cite
|
Sign up to set email alerts
|

Ergovaline binding and activation of D2 dopamine receptors in GH4ZR7 cells

Abstract: Ergovaline inhibition of radioligand binding to the D2 dopamine receptor and ergot alkaloid inhibition of vasoactive intestinal peptide (VIP)-stimulated cyclic AMP production in GH4ZR7 cells, stably transfected with a rat D2 dopamine receptor, were evaluated. Ergovaline inhibition of the binding of the D2-specific radioligand, [3H]YM-09151-2, exhibited a KI (inhibition constant) of 6.9 +/- 2.6 nM, whereas dopamine was much less potent (370 +/- 160 nM). Ergot alkaloids were also effective in inhibiting VIP-stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 18 publications
0
39
0
Order By: Relevance
“…Lolines may be involved in vasoconstriction and vascular thickening, and the site of action may be a-2-adrenergic, D, dopamine, or serotonergic receptors (Larson et al, 1995;Strickland et al, 1996). Also, a significant immunosuppressive effect has been noted in feeding studies in mice (Dew et al, 1990).…”
Section: Activities Of Lolinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Lolines may be involved in vasoconstriction and vascular thickening, and the site of action may be a-2-adrenergic, D, dopamine, or serotonergic receptors (Larson et al, 1995;Strickland et al, 1996). Also, a significant immunosuppressive effect has been noted in feeding studies in mice (Dew et al, 1990).…”
Section: Activities Of Lolinesmentioning
confidence: 99%
“…Often measured are altered neurotransmitter metabolism and reduced prolactin and melatonin levels in blood, indicating an endocrine effect and supporting a dopaminergic mechanism for toxicity. Larson et al (1995) demonstrated that ergovaline had high affinity for D, dopamine receptors. Also, ergovaline acted as an agonist for the vasoactive intestinal peptide, stimulating cyclic AMP production in cultured cells, and this response was mediated via the reaction with the D, dopamine receptors.…”
Section: Activities Of Ergot Alkaloidsmentioning
confidence: 99%
“…The interaction of ergovaline with dopamine receptors is best represented by the suppression of circulating prolactin (Elsasser and Bolt 1987). In vitro studies (Strickland et al 1994;Larson et al 1995) have specifically shown that ergovaline is a D2 dopamine-receptor agonist. Specifically, Larson et al (1995) showed that when ergovaline binds D2 receptors, a second messenger response is triggered that is similar to that of dopamine.…”
Section: Dopaminergic Receptor Involvementmentioning
confidence: 99%
“…(1) Decreased circulating prolactin concentration Ergot alkaloids, such as ergovaline, are D 2 dopamine-receptor agonists that result in a suppression of plasma prolactin concentration (Larson et al 1995). The USA fescue toxicosis literature has demonstrated that circulating prolactin concentration is a very sensitive, but variable, indicator of ergopeptide (ergovaline) modulation of the D 2 dopamine receptor (Oliver 1997).…”
Section: Ergovaline Intakementioning
confidence: 99%